1986
DOI: 10.1016/0165-232x(86)90016-9
|View full text |Cite
|
Sign up to set email alerts
|

Confined compression tests: Outlining the failure envelope of columnar sea ice

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…Timco and Frederking, 1986). The tensile and shear strength vanish for that broken ice (C = 0, and = 0).…”
Section: Description Of the Numerical Modelmentioning
confidence: 92%
See 1 more Smart Citation
“…Timco and Frederking, 1986). The tensile and shear strength vanish for that broken ice (C = 0, and = 0).…”
Section: Description Of the Numerical Modelmentioning
confidence: 92%
“… Timco and Frederking (1986) and were shown to produce appropriate ice forces in the validation tests of Barker and Sayed (2012).…”
Section: Simulation Set-up and Test Casesmentioning
confidence: 99%
“…Timco and Frederking, 1986). The ice is allowed to break (or fracture) if normal stress over any part of the ice cover reaches the tensile strength, .…”
Section: Description Of the Numerical Modelmentioning
confidence: 99%
“…Most recently, Timco and Frederking (1986a) analyzed many of these data for category (a) tests and found that the uniaxial strength of columnar ice could be related to the average stress rate by for horizontally-loaded samples, and for vertically-loaded samples, where a is in MPa, 6 is in MPa s-' (lop3 I k0 I 10") and v, is the total porosity (brine + air) in parts per thousand. Similar expressions have been determined in terms of nominal strain rate.…”
Section: Compressioe Strengthmentioning
confidence: 99%
“…For ice, the failure envelope has been determined by using the combined results of uniaxial compression tests, confined compression tests and shear strength tests both for mostly granular sea ice Frederking, 1983a, 1984), and columnar sea ice (Nadreau and Michel, 1984;Timco and Frederking, 1986a) over a range of loading rates and temperatures. Due to the hexagonal structure of the ice lattice and the horizontal alignment of the c-axis in the columnar ice, there is a marked difference in the failure envelope between the two ice structures (see Fig.…”
Section: Failure Emlopementioning
confidence: 99%